Effects of culture on distance learning in higher education in the light of digital divide and multicultural: Curriculum and design strategies - (:unkn) unknown (My University, 2012)
This paper examines the challenges faced by students who do not belong to the majority culture served by their school. Two related topics will be discussed in the study. The first topic is the situational and dispositional challenges that confront many minority and cross border students in distance education. The second topic is a discussion of the multicultural communication and educational strategies that promote social equity and social justice. The main titles will be situational challenges (digital divide, personal costs, and computer mediated communication), dispositional challenges (field dependent cognitive style, collectivism etc.) and multicultural education. As a result of this paper, as education is still largely a cultural process embedded in diverse national, ethnic, religious, linguistic settings, there are risks that cross border provision does not acknowledge and respect cultural sensitivities. © 2012 IEEE.
Keywords: computer mediated communication; design in distance education; digital divide; distance learning; multicultural education